O-045 Transvenous embolization of spinal epidural arteriovenous fistula with compressive myelopathy. (23rd July 2022) - Madhani, S; Oushy, S; Borg, N; Lanzino, G; Cloft, H; Brinjikji, W
Abstract : Introduction: Spinal Epidural Arteriovenous Fistula (SEDAVF) is a rare form of arteriovenous shunting between the epidural arterial arcade and venous plexus, resulting in arterialization of the epidural plexus. Although the current mainstay treatment of such lesions involves trans-arterial embolization (TAE), we present a case describing an alternate trans-venous embolization (TVE) approach for these lesions. Materials and Methods: An elderly female with lumbar stenosis and neurogenic claudication presented with progressive leg paresthesias and weakness. On imaging, she was found to have a rapidly shunting spinal epidural arteriovenous fistula with seven arterial feeders from T12-L3. The fistula had extradural venous drainage into epidural and paraspinal venous plexuses. No intradural pathology was noted. After a transfemoral vein access, a microcatheter was advanced within the left ascending lumbar vein. A 4 x 8 mm coil was then deployed within the vein followed by injection of liquid embolization agent. Results: Transvenous embolization (TVE) resulted in significant reduction in shunting through the SEDAVF, with a minor residual flow seen from the left L2 artery. To obliterate this, another microcatheter was then navigated through the left L2 artery for TAE with liquid embolization agent (figure 1). Post procedural angiography showed no residual shunting and computed tomography showed stable canal stenosis. She was discharged home the same day at her neurological baseline. Conclusion: TAE although the current mainstay treatment of SEDAVF, carries a risk of reflux into critical arterial branches such as radiculomedullary arteries supplying the spinal cord. TVE is an alternate approach that avoids this complication, increases the likelihood of crossing the fistula due to proximity to the shunt and can be used for treatment of SEDAVFs with multiple arterial feeders. Disclosures: S. Madhani: None. S. Oushy: None. N. Borg: None. G. Lanzino: None. H. Cloft: None. W. Brinjikji: None.